2009
DOI: 10.1109/tgrs.2009.2026052
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of ALOS PALSAR Multipolarization and Polarimetric Data to Crop Classification

Abstract: (1) Agriculture and Agri-Food Canada, 960 Carling Ave., Ottawa (Canada) K1A 0C6, mcnairnh@agr.gc.ca Summary of originally proposed researchMapping and monitoring changes in the distribution of cropland provide information that aids sustainable approaches to agriculture and supports early warning of threats to global and regional food security. This project tested the capability of PALSAR multipolarization and polarimetric data for crop classification. L-band results were compared with those achieved with a C-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
103
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(114 citation statements)
references
References 30 publications
10
103
1
Order By: Relevance
“…Although previous studies demonstrated the benefits of quad-pol data compared to single or dual-pol configurations for crop classification when just one acquisition date was available [22,42], when multi-temporal configurations were tested these differences were minor [8,43]. In fact, some studies [44,45] reported high classification accuracies with just three scenes acquired in key dates in dual-pol configurations, in coincidence with our results. Therefore, it seems that rather than a single-date quad-pol dataset, a multi-date dual-pol option provides enhanced crop classification accuracies.…”
Section: Discussionsupporting
confidence: 87%
“…Although previous studies demonstrated the benefits of quad-pol data compared to single or dual-pol configurations for crop classification when just one acquisition date was available [22,42], when multi-temporal configurations were tested these differences were minor [8,43]. In fact, some studies [44,45] reported high classification accuracies with just three scenes acquired in key dates in dual-pol configurations, in coincidence with our results. Therefore, it seems that rather than a single-date quad-pol dataset, a multi-date dual-pol option provides enhanced crop classification accuracies.…”
Section: Discussionsupporting
confidence: 87%
“…In areas with persistent and pervasive cloud occultation, the costs may outweigh the benefits for monitoring with optical data. SAR data algorithms are currently being prototyped and analyzed for operational monitoring applications [57,64,[95][96][97].…”
Section: Discussion and Future Researchmentioning
confidence: 99%
“…Cloude and Pottier calculated an entropy H and an angle α and then linearly separated the H-α plane into nine zones within a feasible region to determine the basic scattering mechanisms. In recent years, Cloude-Pottier decomposition has been analyzed, improved, and widely applied in segmentation, classification, and detection applications [17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%